IMPLEMENTASI SISTEM GADAI SAWAH DALAM PERSEPEKTIF HUKUM ISLAM DI DESA JAMBE ANOM - Musthafa Syukur; Kholidatul Hasanah (Lafadz Jaya Publisher, 2023)
The practice of pawning rice fields in Jambe anom village has been going on for a long time, for generations, people usually pawn as loan collateral. One of the problems with the practice of pawning rice fields in Jambe anom village is based on an agreement between the two parties, rahin (pledge giver) murtahin (pledge recipient), this agreement is writtwn in thw form letter. The determination of the amount of the mortagage price is not determined by the size of the size of the paddy field/land that will be the collateral, but based on how much money the pawn giver needs until there is an agreement on the amount of money wuth the murtahin (pledge recipient). This research uses a type of qualitative research with a case study appoarch, with tis method intended to obtain data intensively on social phenomena that occur in Jambe anom village. The results of the research are that the practice of pawning rice fields in Jambe anom village based on the opinions is not allowed. Meanwhile, according to Wahbah Zuhaili, this practice is permissible.